When gifted kids don't have all the answers : how to meet their social and emotional needs - Delisle, James R., 1953-; Galbraith, Judy.; Espeland, Pamela, 1951- (Minneapolis : Free Spirits Pub., 2002)
When educators (and parents) think about gifted kids, they usually focus on their intellectual needs. But gifted kids are much more than test scores and grades. In their second book together, Jim Delisle and Judy Galbraith explain what giftedness means, how gifted kids are identified, and how we might improve the identification process. Then they take a close-up look at gifted kids from the inside out-their social and emotional needs. Topics include self-image and self-esteem, perfectionism, multipotential, depression, feelings of'differentness,' and stress. The authors suggest ways to help gifted underachievers and those who are bored in school, and ways to encourage healthy relationships with friends, family and other adults. The final chapter explains how teachers can make it safe to be smart by creating the gifted-friendly classroom. Includes first-person stories, easy-to-use strategies, survey results, activities, reproducibles, and up-to-date research and resources.
Includes bibliographical references and index.
Keywords: Gifted children -- Education -- United States -- Psychological aspects; Classroom environment -- United States